2005
DOI: 10.1007/s00415-005-0894-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of jugular valve insufficiency in patients with transient global amnesia

Abstract: TGA is associated with an increase in the prevalence of jugular insufficiency. Valvular insufficiency may lead to increased venous pressure transmission during a Valsalva maneuver and thus contribute to venous ischemia in TGA. The association of valvular insufficiency and longer reflux times with the occurrence of a trigger event further suggests that cerebral venous congestion is an important etiological factor in transient global amnesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 21 publications
2
42
0
3
Order By: Relevance
“…7 Several mechanisms have been proposed to explain TGA, such as focal arterial ischemia, migraine, epilepsy, and retrograde cerebral venous congestion, 8,9 due to a venous reflux during Valsalva-like activities before symptom onset. [10][11][12][13][14][15] With regard to the first hypothesis, studies have shown that patients with TGA have fewer risk factors for thromboembolic disease than patients with transient ischemic attacks (TIAs); moreover, in patients with TGA the recurrence rate is much lower (usually a single event) and the prognosis for vascular events and mortality is significantly better than in patients with TIAs. 16,17 These findings suggest that arterial thromboembolic disease is an Copyright • C 2014 by the American Society of Neuroimaging 1 unlikely explanation for TGA.…”
Section: Introductionmentioning
confidence: 99%
“…7 Several mechanisms have been proposed to explain TGA, such as focal arterial ischemia, migraine, epilepsy, and retrograde cerebral venous congestion, 8,9 due to a venous reflux during Valsalva-like activities before symptom onset. [10][11][12][13][14][15] With regard to the first hypothesis, studies have shown that patients with TGA have fewer risk factors for thromboembolic disease than patients with transient ischemic attacks (TIAs); moreover, in patients with TGA the recurrence rate is much lower (usually a single event) and the prognosis for vascular events and mortality is significantly better than in patients with TIAs. 16,17 These findings suggest that arterial thromboembolic disease is an Copyright • C 2014 by the American Society of Neuroimaging 1 unlikely explanation for TGA.…”
Section: Introductionmentioning
confidence: 99%
“…The mean duration of the insufficiency jet was the same although patients with a trigger for their global amnesia had longer insufficiency (3.84 sec) than those without triggers (2.55 sec). 85 It remains a matter of debate as to whether the evidence regarding IJV incompetence is circumstantial or definitive in proving the etiology of this syndrome. 86 Occlusion of the jugular bulb catheter after extracorporeal membrane oxygenation resulted in reduced superior sagittal sinus blood flow velocities.…”
Section: Venous Hypertension and Flow Reversals From Nonmultiple Sclementioning
confidence: 99%
“…The presence of jugular valve incompetence (JVI) has been demonstrated to be strongly associated with transient global amnesia (TGA) [1]. In previous studies, JVI (left-sided, right-sided or bilateral) has been identified in up to 85% of patients with TGA, compared to 45% of the controls [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, JVI (left-sided, right-sided or bilateral) has been identified in up to 85% of patients with TGA, compared to 45% of the controls [1,2]. Whether the presence of JVI might represent a specific, underscored, pathogenetic mechanism needs to be clarified.…”
Section: Introductionmentioning
confidence: 99%